Development of a miniature microwave radiothermograph for monitoring the internal brain temperature - Sedankin, Mikhail; Chupina, Daria; Vesnin, Sergey; Nelin, Igor; Skuratov, Victor (Eastern-European Journal of Enterprise Technologies, 2018)
To improve efficiency of non-invasive monitoring of the internal brain temperature, a small-size single-channel microwave radiothermograph consisting of a miniature radiometer and a radiometric sensor based on a printed antenna was developed. Such solution is necessary to provide physicians with a system of non-invasive monitoring of diagnosis and treatment processes. Mathematical modeling and experimental verification of the technical solutions obtained are described in this paper. A miniature radiothermometer was developed. It is a balance modulation radiometer designed on the basis of the R.H. Dicke’s circuit with two loads. Taking into account the requirements of miniaturization, a radiometric sensor was developed by means of numerical simulation. As a result of calculations, optimum antenna dimensions were determined (the total size: ø30 mm, the size of the foil flane substrate: ø23 mm, dimensions of the emitter slot: 16 mm×2 mm). According to the mathematical modeling, the depth of detection of thermal anomalies was not less than 20 mm for the printed antenna which is practically the same as for the waveguide antenna successfully used at present in brain radiothermometry. The standing wave coefficient was determined for various head regions: frontal, temporal, parietal, occipital and the transient between the occipital and parietal regions. Experimental tests of the radiothermograph on water phantoms and biological objects have been carried out. A very good coincidence between the data of numerical simulation and the physical SWR experiment in a range of 1.04–1.8 was obtained. As a result of the study, it has been found that the radiothermograph with a printed slot antenna enabled measurement of internal brain temperature with an acceptable accuracy (±0.2 °C). This will ensure control of craniocerebral hypothermia in patients with brain stroke and allow doctors to promptly change the hypothermia tactics. Small size of the created unit will make it possible to combine it with medical robotic systems to improve treatment effectiveness.